PAJAK PENGHASILAN ENDORSER DALAM PERSPEKTIF SIYASAH SYAR’IYYAH - Risnawati, Risnawati; Sultan, Lomba (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This study aims to determine income tax in the perspective of siyasah syar'iyyah, especially for endorsers. This is a literature research using statutory and syar'i approaches. Astars, celebrities, and celebrities who are endorsers of a product certainly get service fees, and the income earned is calculated as additional income that is the object of taxation. Although there are scholars who forbid the withdrawal of taxes in general, there are also scholars who allow it provided that the withdrawal process cannot be accompanied by mere coercion and power.